IDENTIFIKASI PRODUKTIVITAS KOLONI LEBAH Apis mellifera MELALUI MORTALITAS DAN LUAS ERAMAN PUPA DI SARANG PADA DAERAH DENGAN KETINGGIAN BERBEDA - Tedjo Budiwijono (Jurnal Gamma, 2012)
IDENTIFIKASI PRODUKTIVITAS KOLONI LEBAH Apis mellifera MELALUI MORTALITAS DAN LUAS ERAMAN PUPA DI SARANG PADA DAERAH DENGAN KETINGGIAN BERBEDATedjo BudiwijonoStaf Pengajar Jurusan Produksi Ternak, Fakultas Pertanian PeternakanUniversitas Muhammadiyah Malangemail : Tedjobdw@yahoo.comABSTRACTThe purpose of this study to determine the productivity of bee colonies Apis mellifera through extensive identification and Eraman pupal mortality in areas with different heights. This research is useful to identify the productivity of bee colonies Apis mellifera grazing in areas with different heights through extensive mortality and Eraman pupa on the nest.The materials and tools used in this study is Apis mellifera bee colonies were 32 colonies were cultivated in the village of Oro-oro Ombo District of Stone Town and Village Junrejo Slamet Overlapping District of Malang. The equipment used in this study is the mask, smoker, thermohidrometer, millimeter paper blocks, mica plastic, roll meter, calculator and electrical balance AND GR 200 and stationery. Experimental method used, Apis mellifera colonies sample selected by purposive sampling, and data obtained difference was statistically tested by paired t test paired comparation {}.Research results obtained were not obtained difference {P> 0.05} value Apis mellifera bee mortality in farmed in the village of Oro-oro Ombo Junrejo District of the City of Stone {950 m} with Slamet Village District of Overlapping {597 m}. While extensive Eraman in the first period of March {} not found differences {P> 0.05} in both places and in the period April to two {{} obtained difference P <0.01} in widespread Eraman pupa in District Junrejo City stone 192,11cm2 be increased from 252.04 cm2 and the District Overlapping of 110.85 cm2 to 131.29 cm2.Kay Words : Apis mellifera, and widespread mortality Eraman pupae.